Shariah accountability practice of Malaysian foreign-owned Islamic Banks and Bahrain Islamic Banks / Rosnia Masruki, Hariz Hilmi Khairulannuar and Bablu Kumar Dhar - Masruki, Rosnia; Khairulannuar, Hariz Hilmi; Dhar, Bablu Kumar (UiTM Cawangan Johor, 2019)
Transparency is the epitome of accountability, Shariah accountability is not an exception. The lack of external audit on Shariah compliance in Malaysia to appraise Shariah internal controls is concerning. Presently, a Shariah Committee Report (SCR) is the only report pertaining to Shariah matters that is disclosed by every Islamic bank (IB) in Malaysia. Hence, this study seeks to determine the level of disclosure of the SCR of foreign-owned Islamic banks (IBs) in Malaysia and Islamic banks in Bahrain. Besides, the study also attempts to compare the disclosure practice of SCR between the two countries. The sample comprises five foreign-owned IBs in Malaysia and six IBs in Bahrain. The study uses content analysis for descriptive analysis and rubric to evaluate the SCR based on the latest 2017 annual reports of both countries. This is due to the fact that both countries are practising entirely different standards for accounting and auditing procedures, namely International Financial Reporting Standards (IFRS) and Accounting and Auditing of Islamic Financial Institutions (AAOIFI), Financial Accounting Standards for Malaysia and Bahrain, respectively. The study finds that the level of disclosure of SCR of IB in Bahrain is much higher than Malaysia. These findings entail significant implications for policy makers regarding matters of Shariah Reporting and Shariah Governance, explicating also the needs for future research.